Stacking and Analysis of Melamine in Milk Products with Acetonitrile-Salt Stacking Technique in Capillary Electrophoresis - Yu Kong; Chong Wei; Zhanwu Hou; Zilong Wang; Jiaqiang Yuan; Jiang Yu; Yongxi Zhao; Yuhai Tang; Meili Gao (Journal of Analytical Methods in Chemistry)
Melamine was measured in real milk products with capillary electrophoresis (CE) based on acetonitrile-salt stacking (ASS) method. Real milk samples were deproteinized with acetonitrile at a final concentration of 60% (v/v) and then injected hydrodynamically at 50 mBar for 40.0 s. The optimized buffer contains 80.0 mmol/L pH 2.8 phosphates. Melamine could be detected within 20.0 min at +10 kV with a low limit of detection (LOD) of 0.03 μmol/L. Satisfactory reproducibility (inter- and intraday RSD% both for migration time and peak area was lower than 5.0%) and a wide linearity range of 0.05 μmol/L ~ 10.0 μmol/L were achieved. The proposed method was suitable for routine assay of MEL in real milk samples that was subjected to a simple treatment step.